2020
DOI: 10.3988/jcn.2020.16.1.37
|View full text |Cite
|
Sign up to set email alerts
|

A Cortical Substrate for Square-Wave Jerks in Progressive Supranuclear Palsy

Abstract: Background and Purpose Square-wave jerks (SWJs) are the most common saccadic intrusion in progressive supranuclear palsy (PSP), but their genesis is uncertain. We aimed to determine the characteristics of SWJs in PSP (the Richardson subtype) and Parkinson's disease (PD) and to map the brain structures responsible for abnormal SWJ parameters in PSP. Methods Eye movements in 12 patients with PSP, 12 patients with PD, and 12 age-matched healthy controls were recorded using an infrared corneal reflection device. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…While a number of conditions are associated with specific eye movement deficits, SWJs are not known to be characteristic of any other mental illness. SWJs are present in individuals with neurological conditions such as Friedreich's ataxia (Fahey et al, 2008), progressive supranuclear palsy (Anagnostou et al, 2020) and Parkinson's disease (Otero-Millan et al, 2013), but unlike our findings in AN, they have not been proposed as a biomarker for these illnesses.…”
contrasting
confidence: 99%
“…While a number of conditions are associated with specific eye movement deficits, SWJs are not known to be characteristic of any other mental illness. SWJs are present in individuals with neurological conditions such as Friedreich's ataxia (Fahey et al, 2008), progressive supranuclear palsy (Anagnostou et al, 2020) and Parkinson's disease (Otero-Millan et al, 2013), but unlike our findings in AN, they have not been proposed as a biomarker for these illnesses.…”
contrasting
confidence: 99%
“…Previous studies have reached a similar conclusion [6,14] , but we subsequently conducted subgroup analyses and found that square-wave jerks were more common in ALS patients with bulbar involvement than in ALS patients without bulbar involvement. The genesis of square-wave jerks remains uncertain, and our present ndings are supported by the "brainstem hypothesis" of square-wave jerk generation [33] . This theory, based on the model of Otero-Millan et al [34] , assumes the presence of a disturbance in the brainstem neural circuits.…”
Section: Discussionsupporting
confidence: 79%
“…It was hypothesized that atrophy of temporal cortical structures may lead to overactivity of the superior colliculus, leading to increased activity of excitatory burst neurons and less input to omnipause neurons in the brainstem. In reference to neuropathological characteristics of anti-IgLON5 disease, in which subcortical pTau deposits were found, with isolated tau pathology in the temporal cortex only, this could also explain the presence of SWJ in patients with PSP in which tau pathology is found more prominently over the course of the disease ( 4 , 23 , 26 ). SWJ were observed in 9/10 patients with PSP, but in none of our patients with anti-IgLON5 disease.…”
Section: Discussionmentioning
confidence: 99%